CALLUS REGENERATION OF Chrysanthemum AFTER GAMMA RAY IRRADIATION FOR THE RESILIENCE OF MEDIUM PLAIN - Wijayani, Ari; Muafi, Muafi; Wahyurini, Endah; Lestari, Rina Sri (Journal TECHNO, 2015)
Development of chrysanthemum plants in the medium plains is still facing obstacles due tounfavorable climate. Until today, the availability of tolerant chrysanthemum seeds grown in the mediumplains is not maximized so that the necessary effort in order to increase the genetic diversity as thematerial selection to obtain tolerant chrysanthemums grown in medium plain. This research is beingconducted in order to follow up the problems of availability of tolerant chrysanthemums seeds grown inthe medium plains at several stages. Stage one is the induction of callus after gamma ray irradiation invitro. This research has been conducted in tissue culture laboratory of the Faculty of Agriculture UPN"Veteran" Yogyakarta from February to June 2015. Tested regeneration media is ½ MS with the additionof IAA 0.1 mg/l; 0.2 mg/l; 0.3 mg/l; 0.4 mg/l and 0.5 mg/l. The results showed that ½MS regenerationmedia with the addition of IAA 0.3 mg/l spur sprouts emerge percentage (100%); while growing sprouts(8.67 days), height are about sprouts (3:10 cm) and number of sprout (7:00). Regeneration mediumTreatment with kinetin 2 mg/l + IAA 0.5 mg/l gives the number of root growth (13) and root length (4:07cm)Keywords: Chrysanthemum, tolerant medium plains, in vitro selection, gamma ray irradiation,